2021
DOI: 10.1177/20503121211032810
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms due to COVID-19 and associated factors among healthcare workers in Southern Ethiopia

Abstract: Objectives: Globally, novel coronavirus disease 2019 (COVID-19) has spread rapidly since it was first identified and challenging the provision of essential services for low-resource countries. Healthcare workers involved in providing care are at high risk of developing mental health problems. The aim of this was to determine the prevalence of depressive symptoms due to COVID-19 and associated factors among healthcare workers in the West Guji zone in public health facilities, southern Ethiopia. Methods: A facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The data was collected by using a pretested structured selfadministered questionnaire with data collector guidance. The questionnaire was first prepared in English, then translated into Afaan Oromoo, then translated back into English by fluent speakers to verify its consistency (29). The questions which assess the magnitude of COVID-19-related anxiety, stress, and its associated factors among healthcare workers were adopted from similar previous studies (5, 6, and 11).…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…The data was collected by using a pretested structured selfadministered questionnaire with data collector guidance. The questionnaire was first prepared in English, then translated into Afaan Oromoo, then translated back into English by fluent speakers to verify its consistency (29). The questions which assess the magnitude of COVID-19-related anxiety, stress, and its associated factors among healthcare workers were adopted from similar previous studies (5, 6, and 11).…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Depression is defined as a psychopathologic mood disorder with different severity levels that depend on the number of experienced symptoms and the degree of impairment [ 23 ]. Specific findings on the prevalence of depression during the pandemic show that, even if an individual does not have a severe pathology, most people have experienced the symptoms at some degree, such as lack of motivation, sadness, difficulty to concentrate on tasks, sleeping and eating disorders [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to other studies undertaken in Africa and other LMICs, the overall prevalence of depression reported in this study was low ( Hayat et al, 2021 ; Wilson et al, 2020 ). Studies carried out in Ethiopia also reported a higher prevalence which varied from 20% to 60% ( Ayalew et al, 2021 ; Jemal et al, 2021 ; Mulatu et al, 2021 ; Wayessa et al, 2021 ). The differences in the prevalence of depression observed in these studies may result from the use of various screening tools, survey time, rating scales, or cutoff scores to identify clinically significant levels of depression ( Belete & Anbesaw, 2022 ).…”
Section: Discussionmentioning
confidence: 95%